Outcomes of integrating livelihood into mental health and psychosocial support program among survivors of torture: A mixed-method assessment from western Nepal - Khanal, Diwakar; Sitaula, Sabina; Koirala, Pitambar; Gautam, Kamal; Koirala, Suraj (Torture Journal, 2024)
Introduction: From 1996 to 2006, Nepal experienced a decade-long armed conflict that adversely impacted survivors of torture. The conflict posed threats to various facets of their lives, such as mental health, socio-economic status, human rights, and the process of reintegration into their original communities. This study was done with the survivors of torture from the armed conflict. Objective: This study aims to generate evidence on the impact of livelihood support (supporting individuals with earning their livelihood through business development, farming/animal husbandry and micro-entrepreneurship) upon mental health and psychosocial wellbeing as well as social empowerment of survivors of torture. Results: In total, 44 out of 46 torture survivors reported improvement in their mental health and psychosocial well-being after the livelihood intervention was instituted. Significant reduction in the severity of symptoms of depression (21.7% to 2.3%; P<0.001), anxiety (15.2% to 6.8%; P<0.001), and post-traumatic stress disorder (44.4% to 4.5%; P<0.01) was observed with medium to high effect size. Similarly, improvement in social relationship, economic status, and autonomy (increase in self-confidence and motivation) were noticed post-intervention. Discussion and conclusion: Our study concludes that the livelihood intervention has significantly contributed to economic uplift, improved mental health, psychosocial well-being, social empowerment and quality of life among the survivors of torture. The data provide preliminary evidence of positive outcomes from integrating a livelihood program into an MHPSS (Mental Health and Psychosocial Support) program. Although the lack of a control group prevents us from isolating the specific impacts of the livelihood program, our qualitative data indicate that the intervention is well-received, culturally relevant, and promising. The study has yielded certain recommendations for further research. Keywords: Conflict, survivors of torture, livelihood, mental health and psychosocial support (MHPSS) and social relations.